Carbon dioxide mitigation potential of seaweed aquaculture beds (SABs) - Calvyn F.A. Sondak (2018)
© 2016, Springer Science+Business Media Dordrecht. Seaweed aquaculture beds (SABs) that support the production of seaweed and their diverse products, cover extensive coastal areas, especially in the Asian-Pacific region, and provide many ecosystem services such as nutrient removal and CO2assimilation. The use of SABs in potential carbon dioxide (CO2) mitigation efforts has been proposed with commercial seaweed production in China, India, Indonesia, Japan, Malaysia, Philippines, Republic of Korea, Thailand, and Vietnam, and is at a nascent stage in Australia and New Zealand. We attempted to consider the total annual potential of SABs to drawdown and fix anthropogenic CO2. In the last decade, seaweed production has increased tremendously in the Asian-Pacific region. In 2014, the total annual production of Asian-Pacific SABs surpassed 2.61 × 106 t dw. Total carbon accumulated annually was more than 0.78 × 106 t y−1, equivalent to over 2.87 × 106 t CO2y−1. By increasing the area available for SABs, biomass production, carbon accumulation, and CO2drawdown can be enhanced. The conversion of biomass to biofuel can reduce the use of fossil fuels and provide additional mitigation of CO2emissions. Contributions of seaweeds as carbon donors to other ecosystems could be significant in global carbon sequestration. The ongoing development of SABs would not only ensure that Asian-Pacific countries will remain leaders in the global seaweed industry but may also provide an added dimension of helping to mitigate the problem of excessive CO2emissions.